THE EFFECT OF CONTACT HISTORY AND IMMUNIZATION STATUS ON THE NEW CASE OF LEPROSY - Ulfa Nurzila; Retno Adriyani (Universitas Airlangga, 2019)
Background: The highest new case of leprosy in Indonesia was occupied by East Java Province for four consecutive years, with the number of new leprosy patients as many as 3880 in 2017. Purpose: This study aims to determine the characteristics of individual factors and risks factor for new leprosy cases. Methods: This research is observational analytic research with case control research design. The population of the case is new lepers that were diagnosed since January-September 2018. Meanwhile, the control population is skin poli patients who have not been diagnosed with leprosy and tuberculosis. Sampling technique used was simple random sampling. Variables studied were individual characteristics (age, gender, income) and individual risk factors including immunization status, contact history and population status. Results: Majority of the (57.90%) case respondents never received BCG immunization. 78.90% of the respondents case had history of contact with lepers before. 89.50% of respondents in cases and controls were permanent residents in Mojokerto Regency. Results of analysis of immunization status and contact history has significant influence to the new leprosy case. Status of not having BCG immunization (OR= 5.16; 95% CI= 1.23 <OR <21.55), p= 0.04) and history of having contact with lepers (OR= 6.43; 95% CI= 1, 52 <OR <27.24), p= 0.02) significantly affected new cases leprosy.  Conclusion: There is an influence between non-immunization status and history of contact with new leprosy cases. It is important to carry out early detection of individuals in contact with lepers, especially household contacts and recommendations for repeated BCG vaccination